Clinical outcomes of patients with acute minor stroke receiving rescue IA therapy following early neurological deterioration. (24th April 2015) - Kim, Joon-Tae; Heo, Suk-Hee; Yoon, Woong; Choi, Kang-Ho; Park, Man-Seok; Saver, Jeffrey L; Cho, Ki-Hyun
Abstract : Background: Patients presenting with minor ischemic stroke frequently have early neurological deterioration (END) and poor final outcome. The optimal management of patients with END has not been determined. Objective: To investigate rescue IA therapy (IAT) when patients with acute minor ischemic stroke develop END. Methods: This was a retrospective study of consecutively registered patients with acute minor stroke and END. 'END' was defined as an increase in National Institutes of Health Stroke Scale (NIHSS) scores by 1 or more points (or development of new neurological symptoms) and 'ΔEND−NIHSS' was defined as numerical difference between NIHSS scores at the time of END and before END. Rescue IAT following END was adjusted for the covariates to evaluate the association between IAT and favorable outcome at 3 months. Results: Among 982 patients with acute minor ischemic stroke, END occurred in 232 (23.6%). Of the 209 patients with END with full data available, 87 (41.6%) had favorable outcomes at 3 months. Rescue IAT following END was performed in 28 (13.4%). Favorable 3-month outcomes were seen in 50% of patients undergoing rescue IAT, including 8/19 (42.1%) undergoing rescue IAT beyond 8 h. By multivariate logistic regression analysis, rescue IAT following END was independently associated with favorable outcome at 3 months (OR=10.9; 95% CI 3.06 to 38.84; p<0.001). Conclusions: The results suggest that rescue IAT may be safe and effective when END occurs in selected patients with acute minor ischemic stroke. Further prospective and randomized studies are needed to confirm our results.